Rationalisation de la consommation d’énergie électrique dans les unités industrielles - NACERI Mohammed Kamel; CHATTI Mohammed amine; KOUIDRI Mohammed Ali (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electrotechnique, 2023)
This thesis is a general study on the economic solutions of the energy transition to renewable energies, and the technical and statistical procedures to establish an energy audit as the current context of the rational use of energy. With the increase of the tariffs the energy consumptions intervene more and more in a significant way in the costs of production especially in industry has rightly in electricity that in natural gas representing globally of the turnover and the added value, if in the past the aspects related to the march of the line of production, one relegated to the second plan the preoccupations to eliminate the polluting factors, and to the reductions of the costs in general in a competitive environment marked by a very strong competitiveness. The analysis of the consumptions becomes vital in order to detect the potential improvements and the savings which result from it while spreading has the continuous improvement of the availability and the capacity of the installations the techniques of managements also aim the performance as regards organization of identification of the deposits of productivity and the hunting to the over costs (Measurements, Counting, Analysis) are the master words punctuating an energetic study, One can also take into account renewable energies like economic solutions in this field.
OPTION : Energies renouvelables en électrotechnique.